Metaphorical competence in an EFL context: the mental lexicon and metaphorical competence of Japanese EFL students - Azuma, Masumi (2004)
This thesis on metaphor and metaphor study covers theoretical and practical issues in the past and the present both in the occidental and oriental worlds. Metaphor in rhetoric, cognitive and applied linguistics is described briefly, mostly as a theoretical issue. It states that metaphor was treated as part of rhetoric in the past, however, recently it has developed more broadly into a facet of human cognition. As a practical issue, professional studies assessing metaphorical competence are highlighted, which inform the measurement of metaphorical competence of Japanese learners of English (Japanese EFL students, hereafter). The author developed her original measurement instruments (tests and evaluations of metaphorical competence) to assess the receptive and productive metaphorical abilities of Japanese EFL students. The tests aims to measure Japanese EFL students' metaphorical competence and discover the answers to what factors affect their comprehension and use of English metaphorical expressions and what kinds of metaphorical expressions are salient or opaque for them. This study showed that the Japanese EFL students' receptive ability was better than their productive ability. It further indicated that the size of their mental lexicons, the elasticity of their linguistic ability, the degree of semantic expansion, and their cognitive flexibility (e.g. analogical reasoning, mapping and networking) were important factors affecting their ability to handle metaphorical expressions. Another important discovery was that L1 transfer might play an ambivalent role. As for the salience and opacity of metaphorical expressions, the degree of clarity of expressions was an important element. For example, the expressions with images easy to visualise were the easiest for the Japanese EFL students to understand and use metaphorically. The highly conventional idioms involving metaphorical meanings were problematic for them to understand and especially to use.